an Analysis of KH. Maimoen Zubair’s Social, Political, and Religious Perspectives in Indonesia Through the Qur’anic Tafsir Safīnatul Kallā Sayalamūn - Irfan, Muhammad; Maftuhah, Maftuhah (AL MURABBI, 2025)
Tafsir Al-Qur'an is a reflection of life experienced by its interpreters. and this paper will analyze Kiai Maimun Zubair's response to contemporary issues related to social, political, and religious issues in Indonesia through a study of the book Tafsir Safīnatu Kallā Saya'lamūn.  which was delivered by Kiai Maimun Zubair in Javanese, then translated into Arabic by his student, Lora Ismail Al-Ascholy. Kiai Maimun Zubair is a charismatic Ulama who is widely known by the Indonesian people and even the world not only as an active figure in the pesantren environment, but also has extensive experience in the Indonesian political realm. Therefore, his thoughts and views in understanding the Qur'an are important. The research methods used in this study are descriptive, historical, and explanatory methods, with the application of critical discourse analysis belonging to Teun A. Van Dijk. The results of this study show that KH. Maimoen Zubair not only uses the interpretation of the Qur'an as a means to understand God's words in the Qur'an, but also as a means to express his views and responses to social, political and religious problems in Indonesia. such as agricultural issues, democracy, the independence of the Republic of Indonesia, the spread of Islam in Java, and the security of the Indonesian State received attention from him.  The Safīnatu Kallā Saya'lamūn tafsir not only describes the social, political and religious situation in Indonesia, but also provides solutions and significant contributions in discussing these conformer problems. His attitude reflects the paradigm of thinking of Islamic boarding school scholars who are firm in their attitude and strengthen their beliefs, so that they make the Banayak Islamic boarding school play an active role in the process of building a more advanced and prosperous Indonesia.